2022
DOI: 10.1073/pnas.2116956119
|View full text |Cite
|
Sign up to set email alerts
|

Postmitotic accumulation of histone variant H3.3 in new cortical neurons establishes neuronal chromatin, transcriptome, and identity

Abstract: Histone variants, which can be expressed outside of S-phase and deposited DNA synthesis-independently, provide long-term histone replacement in postmitotic cells, including neurons. Beyond replenishment, histone variants also play active roles in gene regulation by modulating chromatin states or enabling nucleosome turnover. Here, we uncover crucial roles for the histone H3 variant H3.3 in neuronal development. We find that newborn cortical excitatory neurons, which have only just completed replication-coupled… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…This observation might reflect the fact that neuronal differentiation is accompanied by global changes in chromatin modifications 54 . Supporting this idea, recent findings indicate that accumulation of the histone H3.3 isoform in differentiating cortical neurons is important to establish their identity and axonal connectivity 55 . Therefore, the induction and incorporation into nucleosomes of histone H3.3 during cortical neurogenesis could favor the generation of methylation-depleted histones in the presence of K-to-M mutants.…”
Section: Discussionmentioning
confidence: 91%
“…This observation might reflect the fact that neuronal differentiation is accompanied by global changes in chromatin modifications 54 . Supporting this idea, recent findings indicate that accumulation of the histone H3.3 isoform in differentiating cortical neurons is important to establish their identity and axonal connectivity 55 . Therefore, the induction and incorporation into nucleosomes of histone H3.3 during cortical neurogenesis could favor the generation of methylation-depleted histones in the presence of K-to-M mutants.…”
Section: Discussionmentioning
confidence: 91%
“…A recent paper studied the effect of H3f3a and H3f3b co-deletion specifically in developing neurons [ 19 ]. They knocked out H3f3a and H3f3b in neural progenitor cells using Emx1-Cre, and specifically in excitatory neurons after terminal mitosis using Neuro6d-Cre.…”
Section: H33 Double Knockoutmentioning
confidence: 99%
“…They knocked out H3f3a and H3f3b in neural progenitor cells using Emx1-Cre, and specifically in excitatory neurons after terminal mitosis using Neuro6d-Cre. In both situations, knockout mice were born alive but died within a few hours of birth [ 19 ]. These mice show changes to neuronal fate and identity as well as defects in axon projection and development.…”
Section: H33 Double Knockoutmentioning
confidence: 99%
See 1 more Smart Citation
“…Terminally differentiated neurons are believed to have irreversibly exited from the cell division process [ 1 ], and by various means, these cells obtain their postmitotic identity [ 2 , 3 ]. Nonetheless, a large body of work has indicated that as individuals age, a small population of these cells may recommit to a cell cycle-like process [ 4 ], and increasing levels of these events are found in disease-affected brains of patients with late-onset Alzheimer’s disease (AD) [ 4 11 ].…”
Section: Introductionmentioning
confidence: 99%